Effectiveness of Word Craft Teaching Media in English Learning at Senior High School 3 Lamongan - Abelinda, Frisca Adisty; Maghfiroh, Suanah Sevira; Khasanah, Uswatun; Syifa, Hidayatus; Belief, Muhammad Nawfan; An-Nisa, Fatikhatul Lely; Albab, M Ulul; Masfufah, Inajati (Universitas Islam Lamongan, 2025)
This study aims to examine the effectiveness of Word Craft as a medium for learning English argumentation at SMA Negeri 3 Lamongan. This research used qualitative method with contrutivist approach. The sample of this study was 72 students consisting of 36 students of grade XI-9 and 36 students of XI-12 from SMA Negeri 3 Lamongan. Data were collected through participant observation and interviews. Data were analyzed using thematic analysis. Word Craft is an innovative learning media that combines two approaches, namely Problem Based Learning (PBL) and Project Based Learning (PjBL). This media helps students develop critical thinking and argumentation writing skills through meaningful and contextual projects. The results showed that the use of Word Craft media was effective and showed significant improvement in students' cognitive processes, especially in composing argumentative texts. Through this media, students are invited to explore controversial topics, collect supporting evidence, and build logical arguments. The constructivist approach in this medium encourages students to actively construct knowledge through experience with the teacher as a provider of tailored support. The research conclusion emphasizes that Word Craft not only improves students' understanding of argumentation structure, but also prepares them to think critically, participate critically in academic discussions. English teachers can use Word Scaft media as an interactive learning media can substantially improve students' ability to organize and produce coherent argumentative texts. This research is expected to be a reference material for teachers to use interactive learning media with different subjects